An adenosine analog shows high antiviral potency against coronavirus and arenavirus mainly through an unusual base pairing mode - Xiaoying Jia; Xuping Jing; Ming Li; Minli Gao; Yao Zhong; Entao Li; Yang Liu; Rui Li; Guoqiang Yao; Qiaojie Liu; Minmin Zhou; Yuxia Hou; et al. (Nature Communications)
Abstract By targeting the essential viral RNA-dependent RNA polymerase (RdRP), nucleoside analogs (NAs) have exhibited great potential in antiviral therapy for RNA virus-related diseases. However, most ribose-modified NAs do not present broad-spectrum features, likely due to differences in ribose-RdRP interactions across virus families. Here, we show that HNC-1664, an adenosine analog with modifications both in ribose and base, has broad-spectrum antiviral activity against positive-strand coronaviruses and negative-strand arenaviruses. Importantly, treatment with HNC-1664 demonstrate anti-SARS-CoV-2 efficacy in infected K18-human ACE2 mice, with reduced viral titer and mortality, as well as improved lung injury. Enzymology data demonstrate that HNC-1664 inhibits RNA synthesis mainly at the pre-catalysis stage. The cryo-EM structures of HNC-1664-bound RdRP-RNA complexes from both SARS-CoV-2 and LASV reveal an unusual base pairing mode of HNC-1664 in part due to its base modification, thus revealing its great potency in binding but not catalysis. Under certain circumstances, 1664-TP can be slowly incorporated by RdRP through regular Watson-Crick base pairing, as evidenced by enzymology data and an HNC-1664-incorporated crystal structure of the RdRP-RNA complex. Overall, HNC-1664 achieves broad-spectrum characteristics by favoring an alternative base pairing strategy to non-catalytically block RNA synthesis, providing a novel concept for the rational development of NA drugs.